Periodontal disease severity in patients with long COVID and non-COVID-19 - Louisa, Marie; Amalina, Alya; Putranto, Ricky Anggara; Komala, Olivia Nauli; Anggraini, Wita (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Previous research studies have found the persistence of various COVID-19 symptoms even after the patient tested negative on a PCR test; this incident is now known as long COVID. These long COVID symptoms are reported to appear in the oral cavity including long COVID effects on periodontal disease, as both long COVID and periodontal disease release similar proinflammatory cytokines such as Acute phase proteins, CRP, TNF-α, IL-1β, IL-2, IL-6, and IFN-g. Purpose: This study aims to show periodontal-disease severity-frequency distribution in COVID-19 survivors with long COVID and in non-COVID-19 patients. Methods: Patients' secondary data in the Periodontics Clinic Faculty of Dentistry at Trisakti University Dental Hospital (n=40) consisted of 20 samples from COVID-19 survivors who experienced long COVID and 20 samples from the non-COVID-19 group selected according to the inclusion criteria. Afterward, the data was recapitulated and processed into a research report. Results: The distribution percentage of generalized gingivitis was highest in non-COVID-19 patients, while generalized periodontitis was highest in COVID-19 survivors with long COVID. Based on periodontitis staging and grading methods, it is not proven that long COVID increases the severity of the periodontitis. Conclusion: This research shows that the distribution of gingivitis in COVID-19 survivors with long COVID has not increased. Meanwhile, the distribution of general periodontitis increased in survivors with long COVID. However, there was no increased severity of periodontitis based on the staging and grading method of periodontitis in the COVID-19 survivors with long COVID.